2013
DOI: 10.1007/s00441-013-1713-8
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus and adenovirus receptor-positive cells compose the putative stem/progenitor cell niches in the marginal cell layer and parenchyma of the rat anterior pituitary

Abstract: The pituitary gland is a slow generative tissue but actively responds to demands by changing homeostasis. The marginal cell layer (MCL) facing the residual lumen has long been indicated as a stem/progenitor cell niche of the pituitary. On the other hand, the coxsackievirus and adenovirus receptor (CAR), which localizes at the tight-junction of the polarized epithelium, is known to participate in the development, differentiation and regeneration of specified tissues. The present study attempts to characterize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 53 publications
3
63
0
Order By: Relevance
“…These and other markers (including E-cadherin, glial cell line derived neurotrophic factor family receptor alpha 2 or GFRA2, nestin and PROP1) were found in the cells of the marginal zone bordering the cleft (Fauquier et al 2008, Gleiberman et al 2008, GarciaLavandeira et al 2009, Yoshida et al 2011, with a similar expression and organization picture in human pituitary (Garcia-Lavandeira et al 2009. In addition, SOX2 + cells were also found within the gland's parenchyma, mostly occurring in clusters and also expressing SOX9 and E-cadherin (Fauquier et al 2008, Chen et al 2013, Nantie et al 2014, Zhu et al 2015. The marginal zone and parenchymal clusters are proposed to represent plural stem cell niches in the pituitary to enable swift adaptation during (subtle) cell remodeling processes (Vankelecom 2012, Vankelecom & Chen 2014.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…These and other markers (including E-cadherin, glial cell line derived neurotrophic factor family receptor alpha 2 or GFRA2, nestin and PROP1) were found in the cells of the marginal zone bordering the cleft (Fauquier et al 2008, Gleiberman et al 2008, GarciaLavandeira et al 2009, Yoshida et al 2011, with a similar expression and organization picture in human pituitary (Garcia-Lavandeira et al 2009. In addition, SOX2 + cells were also found within the gland's parenchyma, mostly occurring in clusters and also expressing SOX9 and E-cadherin (Fauquier et al 2008, Chen et al 2013, Nantie et al 2014, Zhu et al 2015. The marginal zone and parenchymal clusters are proposed to represent plural stem cell niches in the pituitary to enable swift adaptation during (subtle) cell remodeling processes (Vankelecom 2012, Vankelecom & Chen 2014.…”
mentioning
confidence: 85%
“…In contrast, PRRX2 only emerges after birth from P30 in a subset of the SOX2 + cells . Another mesenchymal marker, VIM, is found co-localized with coxsackie and adenovirus receptor (CAR) in some cells just beneath the marginal cell layer, particularly at neonatal age (Chen et al 2013). CAR has been identified as an additional marker of the (rat) pituitary stem cells in the marginal zone as well as the parenchymal clusters throughout life (Chen et al 2013).…”
Section: :3mentioning
confidence: 99%
“…Finally, a battery of new candidate markers has emerged from recent studies (extensively reviewed in Vankelecom 2010 andChen 2014), including the retinoic acid-producing retinal aldehyde dehydrogenase 1 (Raldh1; Fujiwara et al 2007) and the retinoic acid receptor Rarb (Vankelecom 2010;Vankelecom and Chen 2014); the transcription factors PRRX1 and PRRX2 (expressed in proliferating RP progenitor cells until cell-cycle exit and start of differentiation; Susa et al 2012); the cell-adhesion molecule cadherin-18 (expressed in the MZ in a different pattern than CDH1; Chauvet et al 2009); the coxsackievirus and adenovirus receptor (CAR; Chen et al 2013); the Kr€ uppel-like factor 6 (KLF6; Ueharu et al 2014); and the juxtacrine signaling molecule ephrin-B2 (Yoshida et al 2015). A number of the pituitary stem cell markers identified may be involved in constructing and maintaining the 3D network, in particular the cadherins, ephrins and CAR.…”
Section: Pituitary Stem Cells: Expanding Molecular Portrayalmentioning
confidence: 99%
“…We isolated SOX2 cells expressing GFP from these two regions by microdissection, and demonstrated that their in vitro clonogenic potential did not differ between the two locations (Andoniadou et al 2012). Recent studies from rat have revealed that double-positive SOX2 + /S100β + cells may be further refined through in vivo expression of the gene Cxadr, which codes for coxsackievirus and adenovirus receptor (CAR; Chen et al 2013). Furthermore, expression of E-cadherin and the juxtacrine factor ephrin-B2 reportedly define SOX2 + /S100β + /CAR + cells, both in the marginal epithelium and throughout the parenchyma (Chen et al 2013;Yoshida et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from rat have revealed that double-positive SOX2 + /S100β + cells may be further refined through in vivo expression of the gene Cxadr, which codes for coxsackievirus and adenovirus receptor (CAR; Chen et al 2013). Furthermore, expression of E-cadherin and the juxtacrine factor ephrin-B2 reportedly define SOX2 + /S100β + /CAR + cells, both in the marginal epithelium and throughout the parenchyma (Chen et al 2013;Yoshida et al 2015). Analysing the side population, the Vankelecom group (2010) also reported enrichment in ephrin-B expression in this stem cell-rich compartment; together the data suggested that ephrin-B expression was a hallmark of the population containing PSCs.…”
Section: Introductionmentioning
confidence: 99%